GOLDEN RATIO IN GEOMETRIC PROBLEMS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Problems related to the ratio of triangles and sections that make up the golden ratio are given.